2008
DOI: 10.1074/jbc.c800036200
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Protein Quality Control by the Proteasome Involves Ubiquitination and the Protease Omi

Abstract: We report here that blocking the activity of the 26 S proteasome results in drastic changes in the morphology of the mitochondria and accumulation of intermembrane space (IMS) proteins. Using endonuclease G (endoG) as a model IMS protein, we found that accumulation of wild-type but to a greater extent mutant endoG leads to changes in the morphology of the mitochondria similar to those observed following proteasomal inhibition. Further, we show that wildtype but to a greater extent mutant endoG is a substrate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
131
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(136 citation statements)
references
References 18 publications
4
131
0
1
Order By: Relevance
“…Furthermore, we previously reported that the UPR mt relies on estrogen receptor alpha (ER␣), which confers cytoprotection against proteotoxic stress in the mitochondria (28).…”
mentioning
confidence: 99%
“…Furthermore, we previously reported that the UPR mt relies on estrogen receptor alpha (ER␣), which confers cytoprotection against proteotoxic stress in the mitochondria (28).…”
mentioning
confidence: 99%
“…10 l of each dilution was spotted onto the indi- 4 Kreft and Hochstrasser, unpublished data. cated media using a multichannel Pipetman, and plates were incubated for 2 days at 30°C unless otherwise indicated.…”
Section: Methodsmentioning
confidence: 99%
“…The plasmids pSM2294 (CEN LEU2 VMA12-URA3-HA), pSM2295 (CEN LEU2 VMA12-URA3-HA-CL1), pSM2296 (CEN LEU2 VMA12-URA3-GFP), and pSM2297 (CEN LEU2 VMA12-URA3-GFP-CL1) were generated by PCR-amplifying the VMA12 ORF (lacking its stop codon) from p414MET25-Deg1-Vma12-URA3 4 and recombining into pSM2287, pSM2288, pSM2289, pSM2290, respectively, resulting in the introduction of VMA12 upstream of URA3. The plasmids pSM2298 (CEN LEU2 TOM20-URA3-HA), pSM2299 (CEN LEU2 TOM20-URA3-HA-CL1), pSM2300 (CEN LEU2 TOM20-URA3-GFP), and pSM2301 (CEN LEU2 TOM20-URA3-GFP-CL1) were generated by PCR amplifying TOM20 (lacking its stop codon) from genomic DNA and recombining into pSM2287, pSM2288, pSM2289, pSM2290, respectively, resulting in the introduction of the TOM20 ORF upstream of URA3.…”
Section: Methodsmentioning
confidence: 99%
“…Proteasome-mediated proteolysis is known to be a key checkpoint by which excess or misfolded mitochondrial proteins can be eliminated (27). Therefore, we attempted to assess the ubiquitination level of Mitofilin proteins in the mDISC1 knockdown or truncated mDISC1 overexpression conditions.…”
Section: Disc1-mitofilin Complex In Mitochondriamentioning
confidence: 99%